2013
DOI: 10.1002/phy2.140
|View full text |Cite
|
Sign up to set email alerts
|

The truncated splice variants, NT -PGC - and PGC -1α4 , increase with both endurance and resistance exercise in human skeletal muscle

Abstract: Recently, a truncated peroxisome proliferator-activated receptor gamma coactivator-1 alpha (PGC-1α) splice variant, PGC-1α4, that originates from the alternative promoter was shown to be induced by resistance exercise and to elicit muscle hypertrophy without coactivation of “classical” PGC-1α targets involved in mitochondrial biogenesis and angiogenesis. In order to test if distinct physiological adaptations are characterized by divergent induction of PGC-1α splice variants, we investigated the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
90
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 29 publications
9
90
3
Order By: Relevance
“…In addition, a 12-week progressive weight lifting programme specifically induces isoforms Pgc-1α2, Pgc-1α3 and Pgc-1α4 from the novel promoter [37]. However, other research shows that both promoters can be activated independent of the exercise intervention [60,61]. PGC-1α isoform expression patterns display distinct temporal dynamics [55] and until we understand the mechanisms behind these different expression profiles it is important to unify experimental procedures such as exercise intervention, sampling and gene expression analysis techniques.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…In addition, a 12-week progressive weight lifting programme specifically induces isoforms Pgc-1α2, Pgc-1α3 and Pgc-1α4 from the novel promoter [37]. However, other research shows that both promoters can be activated independent of the exercise intervention [60,61]. PGC-1α isoform expression patterns display distinct temporal dynamics [55] and until we understand the mechanisms behind these different expression profiles it is important to unify experimental procedures such as exercise intervention, sampling and gene expression analysis techniques.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Adding to the discrepant findings, specific truncated splice variants were suggested to be regulated distinctly by two different promoters (Ruas et al 2012), whereas reports focusing on human skeletal muscle demonstrated both exercise modalities upregulate truncated splice variants from both promoters (Norrbom et al 2011, Ydfors et al 2013. It was suggested that the disparate findings might be traced to the use of primers in the Ruas study that do not distinguish between both promoters (discussed in Ydfors et al 2013).…”
mentioning
confidence: 72%
“…The similar responses of splice variants to acute (Ydfors et al 2013, Lundberg et al 2014) and chronic (Lundberg et al 2014) exercise of both modalities in human skeletal muscle challenge this idea of splice variant-specific regulation of adaptation to exercise. Hence, these studies offer two different perspectives.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies have identified several PGC-1α isoforms (Popov et al, 2014;Tadaishi et al, 2011;Ydfors et al, 2013) which are mostly exercise sensitive and collectively contribute to the overall increase in skeletal muscle PGC-1α mRNA observed following exercise (Baar et al, 2002;McGee & Hargreaves, 2004;Pilegaard et al, 2003;Russell et al, 2005). However, PGC-1α protein content may (Mathai et al, 2008) or may not (McGee & Hargreaves, 2004) be up-regulated following acute exercise, indicating that initial increases in PGC-1α mRNA do not necessarily lead to increased protein expression.…”
Section: Pgc-1α In Exercise-induced Mitochondrial Biogenesismentioning
confidence: 99%